Inovasi Monitoring Evaluasi Capaian Fisik dan Anggaran Periodik Kantor Pertanahan Kabupaten Gorontalo - Hendrawana Nur Dengi Lalang; Rusli Isa (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to examine in depth the innovation of periodic monitoring and evaluation of physical achievements and budget implementation at the Land Office of Gorontalo Regency, as a response to the shifting paradigm in public administration. The main focus of the research is to analyze the effectiveness of the digital system employed in enhancing efficiency, accountability, and transparency in program execution. Furthermore, the study seeks to identify the contribution of this innovation to strengthening the principles of good governance and bureaucratic reform, as well as to evaluate its impact on the quality of decision-making and public satisfaction. Using a qualitative approach and case study method, the research is expected to provide strategic recommendations for the development of a more adaptive and results-oriented performance evaluation system in government institutions.